RELIGIOUS EDUCATION IN FORMING STUDENTS' CHARACTER - Ahmad Haerudin, Dodi (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: In Indonesia, character development through education is essential to address moral decay in society. Purpose: This study examines the role of Islamic Religious Education (PAI) in shaping students' character by instilling moral values and ethical behavior. Method: Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation involving PAI teachers, students, and school officials. Result: The research highlights the significant role of PAI in fostering values such as honesty, responsibility, discipline, and mutual respect. Teachers act not only as educators but also as moral role models, guiding students to apply these values in daily life. However, challenges such as limited instructional time, varying religious understandings among students, and insufficient support from families and the community hinder the full potential of character development. Conclusion: This study suggests that schools should integrate religious values across all learning activities and involve parents in the character-building process to better support students in developing strong moral foundations.